The Internalization of Islamic Spiritual Values in Audit Practices: A Study on Auditor Independence - Yudhanta Sambharakreshna (AIBPM Publisher, 2026)
This study examines how Islamic spiritual values are internalized in shaping auditor independence within financial audit practices, particularly in situations involving ethical tension and client pressure. While prior research has largely emphasized regulatory and structural determinants of independence, limited attention has been given to the internal cognitive and ethical processes that guide auditors’ decisions. This study aims to explore how such values are interpreted and enacted in practice. Using a qualitative phenomenological approach, data were collected through in-depth interviews with Muslim auditors from public accounting firms and were analyzed thematically. The findings reveal that four core values: shiddiq (truthfulness), amanah (responsibility), ‘adl (justice), and istiqomah (steadfastness), are internalized through reflective self-regulation and faith-based accountability, which function as intrinsic mechanisms reinforcing objectivity. Auditors consistently described resisting client pressure, maintaining evidence-based judgment, and prioritizing ethical consistency as manifestations of these values. The study concludes that auditor independence is not solely a function of external regulation but is significantly strengthened by the internalization of spiritual values, suggesting the importance of integrating value-based ethical development into professional training.